Climate Denial Fuels Climate Change Discussions More Than Local Climate-Related Disasters - Shah, Miti; Seraj, Sarah; Pennebaker, James W. (Frontiers in Psychology, 2021)
Most scientists agree that climate change is the largest existential threat of our time. Despite the magnitude of the threat, surprisingly few climate-related discussions take place on social media. What factors drive online discussions about climate change? In this study, we examined the occurrence of Reddit discussions around three types of climate-related events: natural disasters (e.g. hurricanes, wildfires), political events (i.e. 2016 US Presidential election), and policy events (i.e. US withdrawal from Paris Climate Agreement, release of IPCC report). The objective was to understand how different types of events influence collective action as measured by discussions of climate change. Six large US cities were selected based on the occurrence of at least one locally-relevant natural disaster in the last decade. Posts (N = 4.4 million) from subreddits of the selected cities were collected to obtain a six month period before and after local natural disasters as well as climate-related political and policy events (which applied equally to all cities). Climate change discussions increased significantly for all three types of events, with the highest discussion during the 2016 elections. Further, discussions returned to baseline levels within two months following natural disasters and policy events but continued at elevated rates for up to four months following the 2016 elections. The findings suggest that collective discussions on climate change are driven more by political leaders’ controversial positions than life-threatening local natural disasters themselves. Implications for collective action are discussed.